PREVALENSI PENYAKIT PINK EYE PADA TERNAK SAPI POTONG DI KABUPATEN MAJENE (Prevalance of pink eye disease in beef cattle in Majene Regency) - Hendro Sukoco; Haeryl Nur Asrar; Muhammad Irfan; Ferbian Milas Siswanto (JURNAL NUKLEUS PETERNAKAN, 2023)
Several diseases have been reported to attack beef cattle in Majene Regency, one of which is Pink Eye. In fact, in 2018, 95 cases of Pink Eye disease were found infecting cattle in Majene Regency. This disease does not cause death, but can cause significant economic losses for breeders. This study aims to determine the prevalence of Pink Eye disease in beef cattle in Majene Regency. The location of the research was carried out in Majene Regency and the time of the research was carried out in October 2022. The method used was quantitative descriptive using secondary data. Data was obtained from the Majene Regency Agriculture, Livestock and Plantation Service regarding the number of Pink Eye cases and beef cattle population in 2019-2021. Data were analyzed using quantitative descriptive analysis. Based on research results, it shows that the prevalence of Pink Eye disease in beef cattle in Majene Regency increased in 2019, namely by 0.390% and in 2020 it became 0.996%. However, in 2021 the prevalence of Pink Eye disease will decrease to 0.352%. Tubo Sendana District has a high number of cases of Pink Eye disease every year. It has even become the sub-district with the highest prevalence in 2021 compared to other sub-districts in Majene Regency. Meanwhile, East Banggae and Pamboang Districts have the lowest number of cases and prevalence compared to other Districts in Majene Regency.